Expression of intercellular adhesion molecule-1 and lymphocyte function-associated antigen-3 on human thyroid epithelial cells in Graves' and Hashimoto's diseases. - Zheng, R; Abney, E; Grubeck-Loebenstein, B; Dayan, C; Maini, R; Feldmann, M (1990)
Human endocrine thyroid epithelial cells (TEC) from autoimmune thyroiditis which express HLA Class II antigens have been shown to present autoantigens to T cells for a TEC-specific immune response. Since the initiation of a specific immune response also involves antigen-receptor independent interactions between accessory molecules, such as lymphocyte function-associated antigen-1 (LFA-1) with intercellular adhesion molecule-1 (ICAM-1) and lymphocyte function-associated antigen-3 (LFA-3) with CD2, it was of interest to determine whether TEC can express the adhesion molecules (ICAM-1 and LFA-3) which augment the efficiency of antigen presentation. Cultured TEC were studied for their expression of ICAM-1 and LFA-3 by immunofluorescence. Those derived from Graves' disease expressed these molecules after stimulation with recombinant human interferon-gamma (IFN gamma) or with recombinant human tumour necrosis factor-alpha (TNF alpha). However, using the same stimuli, TEC from non-toxic goitre were induced to express ICAM-1, but not LFA-3. To establish whether ICAM-1 and LFA-3 on TEC were expressed in vivo during the disease process, antibodies against these molecules were incubated with frozen sections of autoimmune thyroiditis, including Graves' and Hashimoto's diseases, and non-toxic goitre. Both ICAM-1 and LFA-3 were highly expressed in the autoimmune diseases, but not in non-toxic goitre. These findings establish that TEC are able to express adhesion molecules and suggest the possible involvement of these adhesion molecules in the TEC-specific immune response in autoimmune thyroiditis.